2022
DOI: 10.1007/s00210-022-02249-9
|View full text |Cite
|
Sign up to set email alerts
|

Established and emerging treatments for diabetes-associated lower urinary tract dysfunction

Abstract: Dysfunction of the lower urinary tract (LUT) including urinary bladder and urethra (and prostate in men) is one of the most frequent complications of diabetes and can manifest as overactive bladder, underactive bladder, urinary incontinence, and as aggravated symptoms of benign prostate hyperplasia. We have performed a selective literature search to review existing evidence on efficacy of classic medications for the treatment of LUT dysfunction in diabetic patients and animals, i.e., α1-adrenoceptor and muscar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 161 publications
(234 reference statements)
0
13
0
Order By: Relevance
“…There are currently multiple pharmacological options to treat diabetes-induced bladder dysfunctions, notably using α 1 -adrenoceptor and muscarinic receptor antagonists, β 3 -adrenoceptor agonists and phosphodiesterase type 5 inhibitors [ 72 ]. However, here also, newer treatments and drugs are needed to improve long-term efficacy.…”
Section: Rac1 In Non-cancerous Bladder Pathologiesmentioning
confidence: 99%
“…There are currently multiple pharmacological options to treat diabetes-induced bladder dysfunctions, notably using α 1 -adrenoceptor and muscarinic receptor antagonists, β 3 -adrenoceptor agonists and phosphodiesterase type 5 inhibitors [ 72 ]. However, here also, newer treatments and drugs are needed to improve long-term efficacy.…”
Section: Rac1 In Non-cancerous Bladder Pathologiesmentioning
confidence: 99%
“…From a treatment perspective it possibly is more relevant that presence of one or two comorbidities were associated with attenuated treatment responses, but the degree of attenuation was small. Considering that there are no specific treatments for lower urinary tract dysfunction with comorbidities such as diabetes ( Erdogan et al, 2022 ), existing OAB medications remain the best treatment option even if comorbidities are present. Therefore, we consider the present findings to be of pathophysiological and pharmacological interest but propose that they do not justify changing existing paradigms for the clinical management of OAB.…”
Section: Discussionmentioning
confidence: 99%
“…However, little clinical data are available in this regard. There is also limited data on the question whether the combined presence of diabetes and hypertension affects therapeutic outcomes in OAB patients ( Erdogan et al, 2022 ). Therefore, we have used data from two large non-interventional studies in OAB patients ( Amiri et al, 2021 ) to explore the association of diabetes, hypertension and their combination with baseline symptoms of OAB patients and their effect on therapeutic outcomes in a clinically meaningful way under real-world conditions.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 Currently, pharmacotherapy specific to the pathophysiology of DBD, such as mirabegron, may provide potentially effective treatments for these patients. 1,32…”
Section: Discussionmentioning
confidence: 99%
“…29,30 Healthcare providers need to be sensitive in evaluating and discussing UI with patients, since lifestyle modification and behavior therapy with or without pharmacotherapy may help to improve symptoms. 31,32 Currently, pharmacotherapy specific to the pathophysiology of DBD, such as mirabegron, may provide potentially effective treatments for these patients. 1,32 In addition, we observed that the symptom of urgency is not a predictor of treatment-seeking in this study.…”
Section: Discussionmentioning
confidence: 99%